Pre-stressed plates as a mechanism to provide additional under belly blast protection - Darrock, Louis; Manning, Ashley; Caine, Joe; Beadle, James; Peare, Alan; Horsfall, Ian (ISB, 2016)
The use of curved pre-stressed plates is investigated as this provides a possible additional mechanism to resist both initial folding and later structural collapse. Numerical modelling in Autodyn (R) and empirical calculations based on the Westine model were used to determine starting conditions for the explosive trials. Trials were conducted in which plates were pre-stressed by the imposition of a large bending moment from two parallel sides resulting in a tensile stress on the outer surface facing the blast. Tests were conducted at approximately one third linear scale using target plates of 500mm x 500mm and a charge of between 100g and 250g buried in dried sand was used to load them. Unstressed but curved plates were tested and then compared to similar shaped curved plates with an imposed bending stress equal to the yield stress or ultimate tensile stress of the plate material.